DSM-IV und DSM-5: Was hat sich tatsächlich verändert? - Ehret, Anna M.; Berking, Matthias (Verhaltenstherapie, 2013)
The fifth edition of the American Psychiatric Association's Diagnostic and Statistical Manual of Mental Disorders (DSM-5) was published in May 2013. To enable researchers and practitioners to appropriately evaluate and account for advantages and disadvantages, both groups should be informed about amendments to the previous version DSM-IV. In the present paper, we describe the main differences between DSM-IV and DSM-5. Major changes in the overall structure include the discontinuation of the multiaxial system and the revised order of categories. On the level of specific disorders, main differences include the introduction of Major and Mild Neurocognitive Disorders, the extinction of bereavement as an exclusion criterion for Major Depressive Disorder, and the inclusion of Agoraphobia as a distinct disorder. Further additional diagnoses in DSM-5 include Binge-Eating Disorder, Premenstrual Dysphoric Disorder, Disruptive Mood Dysregulation Disorder, Hoarding Disorder, Excoriation (Skin Picking) Disorder, and Caffeine Withdrawal. Categories no longer included in the DSM-5 include Sexual Aversion Disorder and Undifferentiated Somatoform Disorder. Finally, for almost all disorders diagnostic criteria were slightly modified and nosological information was updated. When evaluating the revision, the multiple purposes of the DSM-5 have to be taken into account. As many of these purposes are in conflict or even mutually exclusive, controversial discussions of the new edition by the various interest groups are to be expected.
Created from Fastlane, Scopus look-up
Keywords: Classification systems; Diagnostics; DSM-5; DSM-IV; Mental disorders